ANALISIS PENGENDALIAN WAKTU DAN BIAYA MENGGUNAKAN METODE NILAI HASIL (EARNED VALUE METHOD) PADA PROYEK PERUMAHAN GRAHA CITRA KEMBANGAN DI PT SONTO PROPERTI GRESIK - Akhmad Andi Saputra; Bowo Leksono; Mu'arofah (Wahana Teknik, 2021)
Planning and controlling time and costs are part of the overall construction project management. The existence of significant cost and time deviations indicates poor project management. Cost management and time management activities can be carried out using a method known as the Earned Value Method. The Earned Value Method is used to estimate the end time project completion and project performance. The results of the analysis using the Earned Value Method on the Graha Citra Kembangan housing development project are the project completion time ini accordance with the project qwal plan and the costs incurred are less than the budgeted cost (BAC). The difference between the contract costs (BAC) and the actual costs incurred (ACWP) reached Rp. 36.170.100. There are delays in the completion of work in several weeks of the project cycle. However, at the end of the project completion (week 40), the work was carried out in time according to schedule (estimate project plan time).